2018
DOI: 10.1002/adom.201801303
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium Sulfide Nanosheets for Ultrafast Photonic Device

Abstract: in the field of ultrafast photonics. Since the successful demonstration of graphene-based saturable absorber (SA) for ultrafast pulsed lasers, [7,8] 2D layered materials including black phosphorus, topological insulators, and transition metal dichalcogenides (TMDs), have recently been extensively investigated in nonlinear optical devices for the generation of ultrafast pulses via passive modelocking operation. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] In particular, the recent advancements in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 52 publications
(143 reference statements)
0
35
0
Order By: Relevance
“…Driven by these efforts, mode‐locked fiber lasers based on other layered TMDCs and their derivatives including MoSe 2 , MoTe 2 , WTe 2 , WSe 2 , MoSe 2 , SnS 2 , ReS 2 , In 2 Se 3 , InS, TiS 2 , PtS 2 , PtSe 2 , and HfS 2 , have also developed rapidly, as shown in Table . It can be seen that for these lasers, the minimum pulse width is 67 fs, maximum output power is 212 mW, and maximum repetition rate is 8.82 GHz .…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…Driven by these efforts, mode‐locked fiber lasers based on other layered TMDCs and their derivatives including MoSe 2 , MoTe 2 , WTe 2 , WSe 2 , MoSe 2 , SnS 2 , ReS 2 , In 2 Se 3 , InS, TiS 2 , PtS 2 , PtSe 2 , and HfS 2 , have also developed rapidly, as shown in Table . It can be seen that for these lasers, the minimum pulse width is 67 fs, maximum output power is 212 mW, and maximum repetition rate is 8.82 GHz .…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…Recently, ultrathin HfS 2 , a new member of group IVB (currently called IUPAC group 4) transition metal dichalcogenides, fabricated by mechanical exfoliation or chemical vapor deposition methods was demonstrated to possess nonlinear optical properties as a saturable absorber with saturation intensity about 8 MW cm −2 . [114] Stable pulse train with pulse duration of 222 fs at 1562 nm was achieved in the mode-locking technique. The modulation depth (15.7%) obtainable in HfS 2 nanosheets is higher than that in other 2D materials except WSe 2 and Bi 2 Te 3 .…”
Section: Transition Metal Dichalcogenides (Tmcds)mentioning
confidence: 99%
“…Li et al used exfoliated HfS 2 nanosheets to manufacture memory devices, which exhibited typical bipolar resistive switching behavior with a high switching voltage and a small ratio of high and low resistive states [ 29 ]. Yin et al showed that HfS 2 nanosheets exhibit excellent nonlinear optical absorption in broadband and have the potential for applications in ultrafast photonics [ 30 ]. Hoat et al utilized density functional theory to theoretically investigate the electronic structure and optical properties of HfS 2 monolayers under vertical strain.…”
Section: Introductionmentioning
confidence: 99%